Research on improving deep space communication using hybrid RF-FSO system - Hongzhan LIU; Ting JIANG; Yuan HAO (Tongxin xuebao)
In order to improve the quality of deep space communication,a mixed RF-FSO system and hybrid LPPM-BPSK-SIM scheme were introduced in deep space.The bit error rate of the hybrid RF-FSO system and the FSO system were compared and analyzed under the impact of solar wind fluctuation.The simulation results indicate that the deep space communication system achieves better bit error rate performance by using hybrid RF-FSO system,and the system performance can be further enhanced by adopting hybrid LPPM-BPSK-SIM.